Improving the speaking ability of secondary school students through Community Language Learning (CLL) in the Indonesian context - Muliaty Ibrahim; Andi Miftahul Maulidil Mursyid (Center for Humanities and Innovation Studies, 2018)
This research aimed at finding out whether or not community language learning improves speaking ability significantly better than the conventional method. This research applied the quasi-experimental method. The research data was collected using two kinds of instrument speaking test. The speaking test was given in the form of an interview. The speaking test was to know the students’ achievement on speaking ability toward using community language learning in speaking class. The findings on the speaking ability of the participants were analyzed by using an independent sample t-test. The findings of the study indicated that the result of the post-test was higher than of the pre-test. It means that using community language learning in teaching English with emphasizes on speaking ability to the students’ speaking skill was higher contributed than the conventional method. The study concluded that: Community Language Learning improves the students’ ability to speak English significantly.